Cellular metabolism constrains innate immune responses in early human ontogeny. Issue 1 (December 2018) - Kan, Bernard; Michalski, Christina; Fu, Helen; Au, Hilda; Lee, Kelsey; Marchant, Elizabeth; Cheng, Maye; Anderson-Baucum, Emily; Aharoni-Simon, Michal; Tilley, Peter; Mirmira, Raghavendra; Ross, Colin; et al.
Abstract Pathogen immune responses are profoundly attenuated in fetuses and premature infants, yet the mechanisms underlying this developmental immaturity remain unclear. Here we show transcriptomic, metabolic and polysome profiling and find that monocytes isolated from infants born early in gestation display perturbations in PPAR-γ-regulated metabolic pathways, limited glycolytic capacity and reduced ribosomal activity. These metabolic changes are linked to a lack of translation of most cytokines and of MALT1 signalosome genes essential to respond to the neonatal pathogenCandida . In contrast, they have little impact on house-keeping phagocytosis functions. Transcriptome analyses further indicate a role for mTOR and its putative negative regulatorDNA Damage Inducible Transcript 4-Like in regulating these metabolic constraints. Our results provide a molecular basis for the broad susceptibility to multiple pathogens in these infants, and suggest that the fetal immune system is metabolically programmed to avoid energetically costly, dispensable and potentially harmful immune responses during ontogeny. Little is known about developmental set points of immune responses, especially in humans. Here the authors show that the metabolic state of monocytes isolated from prematurely born infants underlies attenuated responsiveness to fungal infection via selective control of protein translation.